PENGOBATAN TRADISIONAL DALAM NASKAH-NASKAH MINANGKABAU: Inventarisasi Naskah, Teks dan Analisis Etnomedisin - Danang Susena; Pramono Pramono; Herry Nur Hidayat (Jurnal Elektronik WACANA ETNIK, 2013)
Minangkabau old manuscripts have various texts such as Islamic text, history, literature, local custom and tradition, and traditional healing and medicines. The texts on Islam, literature, and local custom have been rapidly studied, but the texts on traditional healing and medicines recieved very little interests and studies.Utilizing the philological approach and etnomedicine, this research was conducted to cover the lack of studies on the texts of traditional healing and medicines which are found in Minangkabau old manuscripts. The data were collected through listing the manuscripts, transliteration and translation, textual criticism and interview. The collected data were analized by qualitative data analysis which was done through three pararel-systimatical steps; data reductions, data presentation and drawing the conclusion.From this research, it is found that the texts of traditional healing and medicines convey the information on Minangkabau traditional healing and medicine including the formula of the medicines and the method of traditional healing. Besides that, it helps to contextually comprehend the concept of illness and the method of healing in the cosmology of Minangkabau society.